Hormonal and non-hormonal oral contraceptives given long-term to pubertal rats differently affect bone mass, quality and metabolism - Porwal, Konica; Sharma, Shivani; Kumar, Saroj; Tomar, Manendra Singh; Sadhukhan, Sreyanko; Rajput, Swati; Kulkarni, Chirag; Shrivastava, Ashutosh; Kumar, Navin; Chattopadhyay, Naibedya (Frontiers in Endocrinology, 2023)
We investigated the effects of hormonal and non-hormonal oral contraceptives (OCs) on bone mass, mineralization, composition, mechanical properties, and metabolites in pubertal female rats given treatments for 3-, and 7 months at human equivalent doses. The combined hormonal contraceptive (CHC) was ethinyl estradiol and progestin, whereas the nonhormonal contraceptive (NHC) was ormeloxifene. NHC increased bone mass in the femur metaphysis after 3 months, but the gain was lost after 7 months. After 7 months, both OCs decreased bone mass and deteriorated trabecular microarchitecture in the femur metaphysis and lumbar spine. Both OCs decreased the mineral:matrix ratio and increased unmineralized matrix after 7 months. After 3 months, the OCs increased carbonate:phosphate and carbonate:amide I ratios, indicating a disordered hydroxyapatite crystal structure susceptible to resorption, but these changes mostly reversed after 7 months, indicating that the early changes contributed to demineralization at the later time. In the femur 3-point bending test, CHC reduced energy storage, resilience, and ultimate stress, indicating increased susceptibility to micro-damage and fracture, while NHC only decreased energy storage. In cyclic loading test, both OCs decreased creep indentation distance, but CHC increased average unloading slope, implying decreased microdamage risk and improved deformation resistance by the OCs. Thus, reduced bone mineralization by the OCs appears to affect bone mechanical properties under static loading, but not its cyclic loading ability. When compared to an age-matched control, after 7 months, CHC affected 24 metabolic pathways in bone and 9 in serum, whereas NHC altered 17 in bone and none in serum. 6 metabolites were common between the serum and bone of CHC rats, suggesting their potential as biomarkers of bone health in women taking CHC. Overall, both OCs have adverse effects on various skeletal parameters, with CHC having a greater negative impact on bone strength.